2010
DOI: 10.1089/pho.2009.2548
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Level Laser Therapy on Pain and Scar Formation After Inguinal Herniation Surgery: A Randomized Controlled Single-Blind Study

Abstract: Infra-red LLLT (830 nm) applied after inguinal-hernia surgery was effective in preventing the formation of keloids. In addition, LLLT resulted in better scar appearance and quality 6 mo postsurgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Many reports demonstrate that LLLT modulates normal dermal fibroblasts and the TGF-β family1. Recently, two clinical reports showed that LLLT was effective in preventing hypertrophic scars and keloids78. However, studies investigating the effect of LLLT on keloid fibroblasts are still rare, especially the ones investigating the effects of LLLT at molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports demonstrate that LLLT modulates normal dermal fibroblasts and the TGF-β family1. Recently, two clinical reports showed that LLLT was effective in preventing hypertrophic scars and keloids78. However, studies investigating the effect of LLLT on keloid fibroblasts are still rare, especially the ones investigating the effects of LLLT at molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is known that laser radiation promotes wound healing [27][28][29]. Moreover, applying the same NIR laser source used in the present study (that is, the same wavelengths and emission mode), we have recently demonstrated the overexpression of NLRP10, a protein involved in the activation of anti-inflammatory pathway, by animal myoblast cells [12,30,31], suggesting that such mechanisms can contribute to the overall therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 57%
“…Everyone present at the site of collection wore safety glasses, suitable to the wavelength used, and we covered the light tip with protective PVC film (Banpack®) to prevent any skin cross-contamination. The PVC film does not cause significant losses in the transmission of low-power laser [37].…”
Section: Methodsmentioning
confidence: 99%